ANALISIS MAYSIR PADA TRANSAKSI PERMAINAN CAPIT BONEKA - agus, sri anggraeni (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Puppet claw game which often occurs in every corner of the city to villages, which is played by all groups, both children and adults, and this game apparently contains "Maysir" gambling content.